Profitability and risk of the mulch-drip irrigation system onion production, Costa Rica - Gómez Alvarado, José Esteban (2022)
The profitability and risk of onion cultivation in Costa Rica in a conventional production system and an alternative system with drip irrigation and mulch were compared. Production costs for both systems and real agricultural prices were estimated, which were important factors in the simulation of profitability scenarios. The results suggest that profitability improves in the alternative production system and risk decreases significantly, which allows mitigating the adverse conditions that the farmer usually faces. Despite the alternative production, onion growers are still exposed to high market risk due to price volatility.